Bridging the technological divide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A policy workshop on research and technology for development was held at the University of Ghana in Legon in late January 2001. Aimed at furthering the ACP-EU dialogue on science and technology policies, it concluded that the key to success lies in...